Ileal Endometriosis - Tjahjadi Robert Tedjasaputra; Marcellus Simadibrata; Diah Rini Handjari (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
Endometriosis at the ileum site is a rare case and among the difficult cases of endometriosis. Intestinal endometriosis may cause obstructing symptoms, which is difficult to be distinguished from malignant or inflammatory disease. We report a case of 33-year-old woman, who admitted to the hospital because of sub-ileus intestinal obstruction. She underwent one session laparoscopy and laparatomy operation. Her ileum showed obstruction because of stenosis and adhesion with an ovarian brown cyst. She experienced terminal ileal resection, ileocaecostomy anastomosis, followed by laparatomy ovarial cystectomy and appendectomy. Microscopic evaluation of the intestine revealed vascular congestion, lymph nodes inflammation, and typical endometrial glands in the muscle layer of ileum. There was no sign of malignancy. These findings led to the diagnosis of ileal endometriosis. The ovarian cyst was actually the endometrial cyst of the ovary.   Keywords: sub-ileus obstructive, ileal endometriosis, endometrial cyst